Enemies of the people [videorecording] - Fairley, John; Marshall, Jill; Welfare, Simon (Red Empire presented by Robert Conquest ; series producer, Gruyneth Hughes, 1990)
Studies the failure of Stalin's five-year plans to turn the Soviet Union with a super power. Stalin blamed secret traitors, executed & imprisoned innocent people especially the political opposition. Includes interior with living people who witness events during Stalin's rule.